COMUNICAREA INTERCULTURALĂ – DIALOG ÎNTRE CIVILIZAŢII - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2011)
The study of communication theory is a multi-disciplinary, multi-dimensional effort. People who write on this topic come from mass communication, film and cinema studies, education, art, anthropology, psychology, philosophy, linguistics, semiotics, and architecture and archaeology among other fields. Mass communication occurs when a small number of people send messages to a large anonymous and usually heterogeneous audience through the use of specialized communication media.